Il turbinio delle immagini Sogni e fantasia nella vita e nelle opere di Pirandello - Valeri, Ludovica (Il sogno della farfalla, 2017)
By reviewing the works and biography of Luigi Pirandello, the article reconstructs the peculiar relationship the writer had with dreams, feelings, and images, both as elements of his stories and as themes for his reflections and research. The depiction of the most relevant events and relationships in Pirandello’s life represents a map which allows us to get oriented in those moments when dreams, reflections on imagination, questions on artistic creation, the narration of invincible and unknown sensations, memories of the past, and characters emerged in his works. The author also analyses the way Pirandello created his stories, how he would “see” them emerge in his mind, how he would follow and subside to them. That which emerges is a relationship which undoubtedly was not simple, often included great difficulties, but was undoubtedly always there and deeply experienced by the Sicilian writer throughout his life.